2009
DOI: 10.1099/ijs.0.001792-0
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomic analyses of clostridia and identification of novel protein signatures that are specific to the genus Clostridium sensu stricto (cluster I)

Abstract: The species of Clostridium comprise a very heterogeneous assemblage of bacteria that do not form a phylogenetically coherent group. It has been proposed previously that only a subset of the species of Clostridium that form a distinct cluster in the 16S rRNA tree (cluster I) should be regarded as the true representatives of the genus Clostridium (i.e. Clostridium sensu stricto). However, this cluster is presently defined only in phylogenetic terms, and no biochemical, molecular or phenotypic characteristic is k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
62
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(63 citation statements)
references
References 48 publications
1
62
0
Order By: Relevance
“…In addition to phylogenetic studies based on comparisons of 16S rRNA gene sequences, Gupta & Gao (2009) identified three conserved indels in three highly conserved proteins (a 4 aa insert in DNA gyrase A, a 1 aa deletion in ATP synthase beta subunit and a 1 aa insert in ribosomal protein S2) that were unique to the species of Clostridium cluster I; these conserved indels were not found in any other known bacterial species for which sequences are available (Gupta & Gao, 2009). Yutin & Galperin (2013) provided a potentially important addition to the restructuring of the clostridia using genomic analyses to investigate Gram-negative-staining sporeformers and other misplaced clostridia.…”
mentioning
confidence: 99%
“…In addition to phylogenetic studies based on comparisons of 16S rRNA gene sequences, Gupta & Gao (2009) identified three conserved indels in three highly conserved proteins (a 4 aa insert in DNA gyrase A, a 1 aa deletion in ATP synthase beta subunit and a 1 aa insert in ribosomal protein S2) that were unique to the species of Clostridium cluster I; these conserved indels were not found in any other known bacterial species for which sequences are available (Gupta & Gao, 2009). Yutin & Galperin (2013) provided a potentially important addition to the restructuring of the clostridia using genomic analyses to investigate Gram-negative-staining sporeformers and other misplaced clostridia.…”
mentioning
confidence: 99%
“…However, taxonomic classification within this branch of the thermophilic Firmicutes relies heavily on 16S rRNA gene phylogeny (33) and phenotype. Alternatively, common concatenated protein sequences were created to construct a phylogenetic tree, which placed C. saccharolyticus with the cellulolytic members of the genus Clostridium (21). Alignment of 16S rRNA gene sequences to construct a phylogenetic tree of the nine deposited Caldicellulosiruptor species revealed that species tend to cluster based on geographical location (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, Gram-positive, anaerobic rods forming endospore were originally assigned to this genus. A phylogenomic and comparative analyses made using data derived from sequenced clostridial genomes allowed to analyse the evolutionary relationships among species of Clostridia (Gupta and Gao, 2009). Clostridium butyricum is the type species of the genus.…”
Section: Taxonomymentioning
confidence: 99%